Manual de los Reglamentos del Agua de Florida: Notas and Glosario - Michael T. Olexa; Laura Minton; Dulcy Miller; Sarah Corbett (EDIS, 2002)
Este es el documento EDIS FE091, una publicación del Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Publicada Novembre 2002.